ANALISIS KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN IPA SISWA SEKOLAH MENENGAH PERTAMA DI KOTA SUNGAI PENUH - Revi Gina Gunawan; Festiyed; Rahadian Zainul; Lufri; Skunda Diliarosta; Rilla Gina Gunawan; Riko Romas Prayuda; Seprianto (EDU RESEARCH, 2024)
In the current educational landscape, critical thinking is an essential skill that significantly aids students in addressing problems effectively. This skill encompasses various aspects such as interpretation, analysis, evaluation, inference, explanation, and self-regulation. The aim of this study is to evaluate the critical thinking abilities of seventh-grade students in Sungai Penuh City, with a specific focus on SMPN 8 and SMPN 11. A total of 60 students from both schools participated in this study, which centered around science education (IPA). A descriptive quantitative method was used, with data collected through essay-based assessments designed around critical thinking indicators. The research results revealed that students from SMPN 8 demonstrated superior critical thinking skills compared to their peers at SMPN 11, with an average achievement score of 46.07% (moderate category) at SMPN 8 and 28.13% (low category) at SMPN 11. The main weaknesses identified were in the areas of analysis and inference, particularly at SMPN 11, where most indicators were classified as low. These findings underscore the challenges present in the learning process, including teaching methods, student motivation, and the learning environment. Therefore, more effective teaching strategies are needed to enhance students' critical thinking abilities, particularly in science education.